A Systematic Analysis Of Effectiveness Of Road Accident Legislation And Its Enforcement Policies In Malaysia - Teo Wei Yap; Arif Fahmi Md Yusof; Norsuhaida Che Musa (Usuli Faqih Research Centre PLT, 2024)
Page: 14 Issue :1 (page: 1-12)